BANKING LAW WITH EMPHASIS ON BANK SECRECY RESPONSIBILITY FOR DIGITAL SECURITY IN FINANCIAL INSTITUTIONS - de Paula, Francinaldo Soares (CIPEEX, 2024)
THIS RESEARCH SEEKS TO EMPHASIZE THE FUNDAMENTAL IMPORTANCE OF BANKING LAW IN THE FACE OF THE ACCELERATION OF DIGITAL TRANSFORMATION IN FINANCIAL INSTITUTIONS, GIVEN THAT THE FINANCIAL MARKET IS CONSTANTLY EVOLVING, A SCENARIO IN WHICH SOME SECURITY MECHANISMS SUCH AS BANKING SECRECY GAIN EMPHASIS AMID RESPONSIBILITY FOR SECURITY DIGITAL IN FINANCIAL INSTITUTIONS. THROUGH ALREADY PUBLISHED BIBLIOGRAPHIC MATERIALS AND EMPIRICAL RESEARCH TO COLLECT DATA IN THE FIELD, THE PROPOSED THEME TOOK SHAPE, FOR BETTER INTERPRETATION IN THE EYES OF THE READER. GOING THROUGH THIS PROCESS, THE METHODOLOGICAL ROUTE USED TO CARRY OUT THE RESEARCH WAS DESCRIPTIVE WITH A QUALITATIVE APPROACH. CONCLUDING AT THE END BY THE GREAT RELEVANCE OF BANKING SECRECY IN THE FINANCIAL INSTITUTION THAT SERVED AS THE STARTING POINT FOR THIS RESEARCH.